Phenolic Assesment of Uncaria tomentosa L. (Cat’s Claw): Leaves, Stem, Bark and Wood Extracts - Navarro Hoyos, Mirtha (2015)
The phenolic composition of extracts from Uncaria tomentosa L. from different regions of Costa Rica was studied using advanced analytical techniques such as UPLC/TQ-ESI-MS and 13C-NMR. Samples from leaves, stems, bark and wood (n = 22) were subjected to extraction to obtain phenolic and alkaloid extracts, separately. Comparatively, higher values of total phenolic content were observed for leaves, stems and bark (225–494 gallic acid equivalents/g) than for wood extracts (40–167 gallic acid equivalents/g). A total of 32 non-flavonoid and flavonoid compounds were identified in the phenolic extracts: hydroxybenzoic acids (benzoic, salicylic, 4-hydroxybenzoic, prochatechuic, gallic, syringic and vanillic acids), hydroxycinnamic acids (p-coumaric, caffeic, ferulic and isoferulic acids), flavan-3-ols monomers [(+)-catechin and (−)-epicatechin)], procyanidin dimers (B1, B2, B3, B4, B5, B7 and two other of unknown structure) and trimers (C1, T2 and one of unknown structure), flavalignans (four unknown structures pertaining to the cinchonain family) and propelargonidin dimers (four unknown structures, reported for the first time in U. tomentosa). Additionally, alkaloid extracts obtained from the plant residue after phenolic extraction exhibited a content of tetracyclic and pentacyclic alkaloids ranging between 95 and 275 mg/100 g of dry material for bark extracts, and between 30 and 704 mg/100 g for leaves extracts. In addition, a minor alkaloid was isolated and characterized, namely 18,19-dehydrocorynoxinoic acid. Our results confirmed the feasibility of U. tomentosa as a suitable raw material for obtaining phenolic- and alkaloid-rich extracts of potential interest.